Centerburg tales - McCloskey, Robert 1914- (New York Puffin Books, 1977)
Further adventures of Homer Price, including those in which a juke box sets the whole town singing against its will and in which a mad scientist develops weeds that overrun the town.
Reprint of the ed. published by Viking Press, New York.
Keywords: Humorous stories